BSTM-03. INCREASING ANTI-TUMOR T CELL ACTIVATION, VELOCITY, AND MIGRATION TO BRAIN STEM GLIOMA USING HEMATOPOIETIC STEM AND PROGENITOR CELLS. (23rd April 2019) - Flores, Catherine; Morley, Cameron; Moore, Ginger; Angelini, Thomas; Mitchell, Duane
Abstract: INTRODUCTION: The survival benefit of adoptive cellular therapy is significantly enhanced by concomitant transfer of bone marrow derived hematopoietic stem cells (HSC) with tumor-reactive T cells in two preclinical models of brain stem glioma (BSG), OB1 (wildtype H3.3), and K2 (H3.3K27M mutation). Using a novel method of 3D printing to fabricate microtumors using BSG cells, we interrogate tumor microenvironment and directly demonstrate that the presence of HSC-derived cells in the microenvironment increases T cell velocity and migration to tumor, and increased tumor cell death. In addition, longitudinal studies in a 3D system allows us to determine properties of tumor cells that escape T cell killing, and differences between T cells that infiltrate tumor bed and those that remain in the peritumoral area. METHODS: We employ an in vitro system using of BSG cells that are 3D printed into a liquid-like solid. Tumor-reactive T cells are generated against BSG cells and printed at distances from the 3D tumoroid to allow migration and T cell patterning studies. Cells retain function and viability in this system for greater than 30 days. Gene expression is used to validate cell properties. RESULTS: We found that HSCs are required for T cell infiltration to orthotopic brain stem glioma in vivo . In our in vitro 3D models of BSG, tumor-reactive T cell velocity of migration and infiltration was significantly increased in the presence of HSCs. Interrogation of T cells that remained adjacent to tumor but did not infiltrate revealed down regulation of chemokines required for migration. In the meantime, tumor cells that escaped T cell killing showed downregulation of MHC-I molecules on their cell surface. These studies are unique in that we are capable of studying biological properties of tumor-reactive T cells that are challenging in vivo.